Analisis Hubungan Populasi Vibrio Dengan Faktor Lingkungan Pada Inlet Tambak Udang Vannamei Di Situbondo - Anita Diah Pahlewi; Ani Listriyana; Creani Handayani (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Vibrio sp. can also be used as an effort to monitor pond water quality. So cultivators must understand the dynamics of pond water quality fluctuations, by periodically controlling pond water quality parameter conditions. The purpose of this study was to determine the relationship between Vibrio populations and environmental factors in Vannamei shrimp ponds. Sampling was carried out for one year in Vannamei shrimp ponds with 4 different locations namely Demung, Panarukan, Jangkar, and Sletreng. Water samples were taken from the inlet (intake channel) in each pond. The data obtained was then analyzed using statistical methods, namely multiple regression analysis. The results of the correlation analysis showed that the relationship between total vibrio and alkalinity and organic matter during the study was shown by a correlation value of R = 0.226, which means the correlation between alkalinity and organic matter to total vibrio was 0.226. The R² value indicates a coefficient of determination of 0.51, which means that the effect of alkalinity and organic matter on total vibrio is very weak, namely 5.10%.